1977
DOI: 10.1136/jcp.30.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Serological grouping of streptococci by a slide coagglutination method.

Abstract: SUMMARY A new method for the serological grouping of streptococci by coagglutination with specific antibodies adsorbed to protein A-containing staphylococci has been assessed. A total of 242 strains of streptococci, including ,-haemolytic streptococci of groups A, B, C, F, and G, Streptococcus pneumoniae and Strep. faecalis were studied. All streptococci of groups A, B, C, and G, groupable by standard methods, were correctly grouped by coagglutination, although 7-3 % showed varying degrees of cross-agglutinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
5
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
(7 reference statements)
4
5
0
Order By: Relevance
“…Numerous investigations have shown that coagglutination testing, particularly with the Phadebact Streptococcus Test, affords the clinical microbiologist a rapid and reliable method to serogroup beta-hemolytic streptococci (10,16,17). The present investigation confirms the diagnostic potential of this method and shows the capabilities of the relatively new SeroSTAT and Streptex latex agglutination tests for the serogrouping of beta-hemolytic streptococci.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Numerous investigations have shown that coagglutination testing, particularly with the Phadebact Streptococcus Test, affords the clinical microbiologist a rapid and reliable method to serogroup beta-hemolytic streptococci (10,16,17). The present investigation confirms the diagnostic potential of this method and shows the capabilities of the relatively new SeroSTAT and Streptex latex agglutination tests for the serogrouping of beta-hemolytic streptococci.…”
Section: Discussionsupporting
confidence: 79%
“…c +, Weak response; -, no response. d Other bacteria tested: Citrobacter diversus (5), Enterobacter cloacae (10), Escherichia coli (10), P. aeruginosa (10), Serratia liquefaciens (10), viridans streptococci (8).…”
Section: Discussionmentioning
confidence: 99%
“…Surface fibrillar structures (M. Jacques et al, submitted for publication) as weil as hemagglutinins (17) of S. suis have recently been described and would support this theory. Also, nonspecific agglutinations among different streptococci were described earlier (11,12). Not only may the nonspecific agglutination described here with reference strains occur, but other agglutinations among field isolates (unpublished observations) which would make absorption of antisera useless may also occur.…”
Section: Resultssupporting
confidence: 53%
“…Methods of bacterial agglutination by specific antisera are frequently used for their detection (CARTER and RYAN 1975, FINCH and PHILLIPS 1977, KHOURY et al 1973, KoDAMA and ISHIMOTO 1976, MASSEY and MANGIAFICO 1974, SATO and DiENA 1974. The direct agglutination procedure in tubes or on slides is simple and relatively sensitive.…”
mentioning
confidence: 99%